2010
DOI: 10.1194/jlr.m004929
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids regulate hepatic gluconeogenic genes and farnesoid X receptor via Gαi-protein-coupled receptors and the AKT pathway

Abstract: Bile acids are important regulatory molecules that can activate specific nuclear receptors and cell signaling pathways in the liver and gastrointestinal tract. In the current study, the chronic bile fistula (CBF) rat model and primary rat hepatocytes (PRH) were used to study the regulation of gluconeogenic genes phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G-6-Pase) and the gene encoding short heterodimeric partner (SHP) by taurocholate (TCA). The intestinal infusion of TCA into the CBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 50 publications
2
88
0
Order By: Relevance
“…Activation of the AKT pathway by conjugated bile acids was shown to activate glycogen synthase activity in vitro and in vivo in a Gi-dependent manner (10). Further, conjugated bile acids were shown to repress the gluconeogenic genes, phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase), both in vitro and in vivo (42). Importantly, repression of PEPCK and G6Pase mRNA by conjugated bile acids was shown to be pertussis toxin sensitive in primary rat hepatocytes.…”
Section: Conjugated Bile Acids Activate S1pr2mentioning
confidence: 95%
See 1 more Smart Citation
“…Activation of the AKT pathway by conjugated bile acids was shown to activate glycogen synthase activity in vitro and in vivo in a Gi-dependent manner (10). Further, conjugated bile acids were shown to repress the gluconeogenic genes, phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase), both in vitro and in vivo (42). Importantly, repression of PEPCK and G6Pase mRNA by conjugated bile acids was shown to be pertussis toxin sensitive in primary rat hepatocytes.…”
Section: Conjugated Bile Acids Activate S1pr2mentioning
confidence: 95%
“…Importantly, repression of PEPCK and G6Pase mRNA by conjugated bile acids was shown to be pertussis toxin sensitive in primary rat hepatocytes. Finally, it was reported that activation of the AKT pathway was required for optimal induction of small heterodimer partner (SHP) mRNA, an FXR target gene, by conjugated bile acids in vivo (42). It has also been reported that activation of the ERK1/2 pathway plays an important role in regulating the rate of turnover of SHP protein (43).…”
Section: Conjugated Bile Acids Activate S1pr2mentioning
confidence: 99%
“…Nutritional Regulation of Endogenous BA Metabolism Modulates High Fat Diet-induced Hyperglycemia-Oral BA treatment reduces hyperglycemia in mice (12), possibly through reduced hepatic glucose output by repression of the Pck1 gene expression (13,14). In addition, PPAR␤/␦ activation reduces hepatic glucose output and improves peripheral glucose disposal (67).…”
Section: Nutritional Regulation Of Endogenous Ba Metabolism Modulatesmentioning
confidence: 99%
“…Glucose metabolism is also regulated by bile acids, and mice treated with cholic acid are protected from diet-induced hyperglycemia (12) and have down-regulated liver expression of the gluconeogenic phosphoenolpyruvate carboxykinase (Pck1) gene (13,14). Furthermore, Fxr Ϫ/Ϫ mice are glucose-intolerant and insulin-resistant, and insulin signaling is blunted in several tissues (15)(16)(17).…”
mentioning
confidence: 99%
“…15,16 Additionally, bile acids have been shown to rapidly activate G-protein coupled receptor(s), which activate the AKT insulin-signaling pathway. Japanese investigators demonstrated that bile acids, by stimulating the bile acid membrane receptor TGR5 (Takeda G-protein coupled receptor clone 5) release Glucagon like Peptide 1 (GLP1) from enterocytes lead to insulin secretion and glycogen synthesis.…”
Section: Discussionmentioning
confidence: 99%